An Empirical Study on the Influence of Consolidated Financial Statement’s Amplification Effect on Audit Fees - Ximing Zhan; Mengying Zhao; Lijuan Yan (Discrete Dynamics in Nature and Society)
As the investing enterprise brings the invested enterprise into the consolidation scope, the number of the items in the consolidated financial statements is enlarged relative to the parent company’s financial statements, which is called the amplification effect of the consolidated financial statements. Using a sample of A-share listed companies in China from 2007 to 2019, this paper investigates the impact of consolidated financial statements’ amplification effect on audit fees. We find that the amplification effect of consolidated financial statements is positively related to audit fees, and the audit risk plays a mediating role. More specifically, the amplification effect of consolidated financial statements increases the audit risk and then increases the audit fees. Furthermore, the effect is more significant in state-owned enterprises (SOEs). This study contributes to a comprehensive understanding of the economic consequences of accounting standards for consolidated financial statements.